#### Answer

$f^{-1}(1)=0$
$f^{-1}(3)=4$

#### Work Step by Step

We see from the graph that $f(0)=1$. This means that $f^{-1}(1)=0$ ($x$ and $y$ get switched). Similarly, we see from the graph that $f(4)=3$ and therefore $f^{-1}(3)=4$.

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

$f^{-1}(1)=0$
$f^{-1}(3)=4$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.